2015
DOI: 10.1364/oe.23.010040
|View full text |Cite
|
Sign up to set email alerts
|

Development of time-domain differential Raman for transient thermal probing of materials

Abstract: A novel transient thermal characterization technology is developed based on the principles of transient optical heating and Raman probing: time-domain differential Raman. It employs a square-wave modulated laser of varying duty cycle to realize controlled heating and transient thermal probing. Very well defined extension of the heating time in each measurement changes the temperature evolution profile and the probed temperature field at μs resolution. Using this new technique, the transient thermal response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 23 publications
(34 reference statements)
1
28
0
Order By: Relevance
“…Only Raman thermometry which is based on the scattering photon energy of the probe light rather than the light intensity can be effective to define temperature differential in such a small scale. probing light might be a good choice, which is being attempted in Wang's lab [128].…”
Section: Challenges Confronted In Current Thermal Characterization Tementioning
confidence: 99%
See 1 more Smart Citation
“…Only Raman thermometry which is based on the scattering photon energy of the probe light rather than the light intensity can be effective to define temperature differential in such a small scale. probing light might be a good choice, which is being attempted in Wang's lab [128].…”
Section: Challenges Confronted In Current Thermal Characterization Tementioning
confidence: 99%
“…Precedent work includes the successful measurement of thermal diffusivity of silicon cantilever [128,129]. and CNT fiber [130].…”
Section: Challenges Confronted In Current Thermal Characterization Tementioning
confidence: 99%
“…2a. Combined with the boundary conditions, the spatially averaged temperature rise in the heated region can be expressed as [29]…”
Section: Experimental Principle and Details 21 Experimental Principlementioning
confidence: 99%
“…Recently, it was reported that a time-domain differential Raman (TD-Raman) thermometry was developed by modulating the excitation laser and probing transient Raman scattering during the pulsed heating circle [29]. In this work, the thermal diffusivity of a silicon cantilever was measured to validate the measurement capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation